POLITENESS STRATEGIES USED BY SANTRI (MALE STUDENTS) AND USTADZ (MALE TEACHERS) IN THEIR INTERACTION AT PESANTREN SALAF ALQURAN SHOLAHUL HUDA AL-MUJAHIDIN MALANG - Bahrudin Nur Aziz Zakaria, 121211231032 (2016)
This study is concerned with politeness strategies used by santri (male student) and ustadz (male teacher) at Pondok Pesantren Salaf Al-Quran Sholahul Huda Al-Mujahidin Malang. The politeness strategies responses were given by santri and ustadz based on hypothetical situation provided. Five teachers or ustadz of Pesantren Salaf Al-Quran Sholahul Huda Al- Mujahidin and 20 students or santri were choosen as the participants. Further more, a qualitative approach by giving questionnaire was employed as the method of the study. To figure out the phenomenon, Brown and Levinson’s (1987) theory of politeness strategies was applied in analyzing the data. From the analysis, it was figured out that all types of politeness strategies were realized both in students’ and teachers’ answers. In formal situation, santri tend to use negative politeness strategy with 40,58%, while ustadz tend to use off record strategy with 44,00%. On the other hand, in informal situation, still santri tend to use negative politeness strategy with 60,14%, while ustadz tend to use positive politeness strategy with 48,00%. It was identified that the three social factors of power, social disntance and ranking of imposition triggered the students and teachers to perform such strategies. The theory of this social factors also proposed by Brown and Levinson (1987). However, another influential factor that was found to encourage the participants to employ those strategies was that Pesantren Salaf Al-Quran Sholahul Huda Al- Mujahidin’s culture that encompasses several values, among of them is politeness, which are based upon the Islamic values declared in Al Quran and Al Hadith.